Evidence synthesis for guideline development of a rare disease — chronic hypoparathyroidism - Yao, Liang (My University, 2023)
Rare diseases currently impact over 250 million people worldwide, accounting for over 3.5% of the global population. Clinicians caring for individuals living with rare diseases face difficulties providing accurate diagnosis and effective treatments. The low prevalence of individual rare diseases, and limited data and constrained resources available for research, makes it challenging to develop useful clinical guidelines. The objective of this thesis is to share our experience in conducting evidence synthesis for the guideline development of a rare disease—chronic hypoparathyroidism, and show how we addressed the challenges encountered during the review process. The thesis begins by describing the challenges of evidence synthesis for guideline development in the context of rare diseases. I then present our strategies to overcome these challenges in three systematic reviews prepared for a chronic hypoparathyroidism guideline. The thesis ends by summarizing the challenges and solutions, highlighting strengths and limitations, and describing opportunities and challenges for future research in evidence synthesis for rare diseases.
Keywords: Rare disease; Chronic hypoparathyroidism; Evidence synthesis; guideline development